Base mediated approach for the synthesis of deoxybenzoins using γ-aryl-β-ketoesters and benzoyl chlorides - Choudhary, Shailendra Singh; Darole, Ratanamala S.; Krishna, Gamidi Rama; Senthilkumar, Beeran (RSC Advances, 2025)
This study introduces a one-pot, transition metal-free strategy for synthesizing deoxybenzoins, overcoming the challenges of conventional methods. The reaction involves dual acylation of gamma-aryl beta-keto esters using K2CO3 in dioxane at 90 degrees C, followed by a concerted transformation to form deoxybenzoin. The protocol operates under mild conditions, tolerates a broad range of substrates, and produces minimal by-products, making it a practical, scalable alternative for accessing pharmaceutically relevant deoxybenzoins.